Antioxidant and cytotoxicity activity of phenolic compounds from Piper sarmentosum Roxb. against T47D human breast cancer cell - Ghazali, Nor Farahiyah; Mustafa, Farah Farisha; Tengku Muhammad, Tengku Sifzizul; Ibrahim, Maizatul Akma (Bentham Science, 2019)
Background: Cancer is a major public health burden worldwide. Breast cancer tops the chart as the most common cancer today and has become the major cause of death in female population. Approximately 60% of currently applied cancer drugs are derived from natural sources. Piper sarmentosum Roxb. is one of natural plants that had been used as herbal medicine. Phytochemical compounds from this plant have become important in the promotion of human health, mainly due to their phenolic compounds, which have been linked with various biomedical properties.